1-D NiO nanorods pillared 2-D MnO2 nanosheets as lithium-free cathode materials for charged-state lithium batteries. (8th June 2021) - Hewavitharana, Indika K.; Ding, Yi; Simon Ng, K.Y.; Deng, Da
Graphical abstract: Highlights: Preparation of three-dimensional porous NiO pillared δ-MnO2 nanoarchitectures as lithium-free cathode materials. NiO pillared δ-MnO2 nanoarchitecture has resulted in a moderately high specific capacity of 185 mA h g −1 . Improved electrochemical performances could be attributed to NiO pillared δ-MnO2 nanoarchitectures. Insertion of pillars is a promising strategy to achieve performances close to theoretical values for monolayer MnO2 sheets. Abstract: Theoretically monolayer MnO2 sheets have an impressive high capacity of 616 mAh/g, but practically monolayer MnO2 sheets have poor performances due partially to monolayer restacking. In this paper, we report the preparation of three-dimensional porous NiO nanorod pillared δ-MnO2 nanosheets as integrated nanoarchitectures as lithium-free cathode materials. The as-synthesized NiO pillared δ-MnO2 nanosheets have resulted in a moderately high specific capacity of 185 mA h g −1, with more than 63% capacity retention after 200 cycles. In comparison, 2D MnO2 nanosheets without NiO pillared structures only achieved a low initial capacity of 137 mA h g −1, with just 17% capacity retention after 200 cycles. The dramatically improved electrochemical performances could be attributed to high surface areas with excellent porosity which provides more electrochemically active sites and thermodynamically favorable insertion pathways for the lithium ions. Our results reveal that insertion of pillars is a promising strategy to explore in order to mitigate the restacking issues and achieve electrochemical performances close to theoretical values for monolayer MnO2 .